Early Detection of Suspected Systemic Lupus Erythematosus in Community-Dwellings in West Java Indonesia - Nadia Gita Ghassani; Laniyati Hamijoyo; Soeseno Hadi (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Prevalence of systemic lupus erythematosus (SLE) has been known in almost all countries around the world. Contrary to this, in Indonesia, neither a national epidemiologic study on SLE nor any direct study on SLE in the general population has been conducted. Early detection of SLE is needed as a first step to determine prevalence of SLE in Indonesia as well as to prevent further complications. This study aimed to obtain the prevalence of suspected SLE in community-dwellings.Methods: This study was conducted in the period September to November 2015 and used the descriptive cross-sectional method. The respondents were people who were at least 18 years old and lived in selected blocks in three different villages in Jatinangor, West Java. Data were obtained from secondary sources of a previous SLE screening study that was incorporated in a study on “Epidemiology of hypertension and albuminuria in Jatinangor” in 2014, using the multistage sampling method. Suspected SLE was based on the Liang screening questionnaire. The collected data were presented in tables.Results: There were 72 respondents (8%) suspected to have SLE. Most of the cases were female (Odds ratio:1.47) and 51–60 years old. The most clinical manifestation was painful swollen joints >3 months.Conclusions: The existence of suspected SLE cases in Jatinangor’s population, as an example of Indonesian population should be a concern so that examinations could be carried out to make sure that respondents with SLE can be provided prompt interventions to prevent further complications.